5-Aminolevulinic acid photoactivated over planktonic and biofilm forms of Enterococcus faecalis as a pharmacological therapy alternative - Adriana Beltran-Leal; Abraham Muñoz-Ruiz; Vicente Esparza-Villalpando; Yolanda Castro; Amaury Pozos-Guillen; Héctor Flores (Universidade de São Paulo, 2020)
The purpose of the study was to evaluate the antibacterial effect of protoporphyrin IX (PpIX) generated by the exogenous administration of 5-aminolevulinic acid or δ-ALA and activated with an argon laser over a planktonic and biofilm of Enterococcus faecalis (E. faecalis) as a pharmacological therapy alternative. A planktonic strain of E. faecalis was cultured with a solution of ∂-ALA (40 µg/mL)-thioglycolate solution for 13 min, and a biofilm of E. faecalis was cultured in a δ-ALA (80 µg/mL)-thioglycolate solution for 13 min. Then, both were irradiated with an argon laser. Finally, the antibacterial effect was evaluated by counting the CFU in planktonic form, and a LIVE/DEAD viability cell test. The production and accumulation of PpIX from exogenously administered δ-ALA on E. faecalis in planktonic and biofilm forms was confirmed by spectrofluorometry. The irradiation of PpIX with an argon laser produced an antibacterial effect on E. faecalis in planktonic and biofilm form, even without biofilm disruption, at a concentration of 40 µg/mL and 80 µg/mL of δ-ALA, respectively. The exogenous administration of δ-ALA in combination with laser irradiation on planktonic and biofilm forms of E. faecalis produces an effective antibacterial effect as complement or alternative to pharmacological therapies.